Radiolabeled Nanoparticles for Cancer Diagnosis and Therapy - Koziorowski, Jacek; E. Stanciu, Adina; Gomez-Vallejo, Vanessa; Llop, Jordi (Anti-Cancer Agents in Medicinal Chemistry, 2017)
Cancer remains as one of the major causes of death worldwide. The emergence of nanotechnology has opened new avenues for the development of nanoparticle (NP)- based diagnostic and therapeutic tools. NPs of different chemical composition, size, shape and surface decoration can be prepared using a wide variety of synthetic strategies. Subsequent radiolabelling with positron or gamma emitters results in potential diagnostic agents which may offer improved selectivity and/or specificity for the target organ or tissue, enabling the acquisition of images with higher signal-to-contrast ratio. Incorporation of alpha or beta emitters leads to therapeutic agents with application in the field of radiotherapy. Here, we first describe the different labeling strategies reported so far for the incorporation of radionuclides into NPs. Recent advances in the use of nanoparticulate constructs both in the diagnostic and therapeutic arenas are then discussed and examples of their application are briefly discussed.
Keywords: nanoparticles